Ireland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2022)
Ireland has considerably strengthened financial sector regulation and supervision since the 2016 FSAP, aided by the ECB/SSM, and is working with European and international regulators to strengthen oversight of the large market-based finance (MBF) sector. This strengthening is evidenced by a successful navigation through the challenges of Brexit and the pandemic. Despite global headwinds, Ireland is exiting the pandemic with strong economic growth and a highly capitalized and liquid banking system. The financial system has grown rapidly and in complexity, especially after Brexit, and Ireland has become a European base for large financial groups. The MBF sector has grown to the second largest in Europe, with global interlinkages.